Cover Image, Volume 40, Issue 3. Issue 3 (10th February 2019) - Rehman, Atteeq U.; Najafi, Maryam; Kambouris, Marios; Al‐Gazali, Lihadh; Makrythanasis, Periklis; Rad, Abolfazl; Maroofian, Reza; Rajab, Anna; Stark, Zornitza; Hunter, Jill V.; Bakey, Zeineb; Tokita, Mari J.; et al.
Abstract : On the Front Cover : This cover image is based on the Rapid Communication Biallelic loss of function variants in PPP1R21 cause a neurodevelopmental syndrome with impaired endocytic function by Atteeq U. Rehman et al., Pages 267–280. DOI:10.1002/humu.23694 .